2009
DOI: 10.1111/j.1467-9701.2009.01179.x
|View full text |Cite
|
Sign up to set email alerts
|

Spillovers from Multinationals to Heterogeneous Domestic Firms: Evidence from Hungary

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
6

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 43 publications
1
27
0
6
Order By: Relevance
“…In line with Békés et al (2009) who show that firms' size and productivity are potential drivers of the intensity of spillover effects and other recent literature that stresses the importance of firm level heterogeneity in analyzing firms (see e.g. Melitz, 2003 andHelpman et al, 2004), we allow the timing of entry pattern to differ according to absorptive capacity and firm size.…”
Section: Firm-level Heterogeneitymentioning
confidence: 66%
“…In line with Békés et al (2009) who show that firms' size and productivity are potential drivers of the intensity of spillover effects and other recent literature that stresses the importance of firm level heterogeneity in analyzing firms (see e.g. Melitz, 2003 andHelpman et al, 2004), we allow the timing of entry pattern to differ according to absorptive capacity and firm size.…”
Section: Firm-level Heterogeneitymentioning
confidence: 66%
“…Damijan et al (2003) and Konings (2001) found no evidence of intraindustry spillovers from foreign-owned firms to domestic firms. However, Békés et al (2009) and Halpern and Muraközy (2007) found evidence of productivity spillovers from FDI firms to domestic firms. The results are more consistent in terms of foreign trade.…”
Section: Related Literaturementioning
confidence: 91%
“…In small and micro enterprises training is often unplanned and spontaneous (Vallence, 1997) and such firms are unlikely to have dedicated training staff (Hawke, 1998). This issue merits particular attention in Hungary, which has many SMEs, mainly domestically owned and with lower levels of productivity and technology (Brown, Earle and Telegdy, 2004;Békés, Kleinert and Toubal, 2006). Greater involvement of foreign firms in work-based initial training would improve the acquisition of technology related skills.…”
Section: Ensuring Workplace-based Training Of High Qualitymentioning
confidence: 99%